The Effect of Listening to Murotal Al-Quran on Anxiety of Pregnant Women with Preeclampsi - Ulaa, Maratun; Marlin, Riska; Yuniza, Yuniza; Azmi , Khusnu Tisa; Puryanti , Feby (Newinera Publisher, 2024)
Preeclampsia is a special condition of pregnancy characterized by hypertension and proteinuria after 20 weeks of gestation in women who had normal blood pressure before pregnancy. Pregnancy with preeclampsia can cause anxiety due to fear and worry felt by pregnant women towards themselves and their babies. This study aims to analyze the effect of listening to murottal Al-Quran on the anxiety of pregnant women with preeclampsia. The research method used was pre-experiment with one group pre-post design to determine the effect of listening to Murottal Al-Quran on the anxiety of pregnant women with preeclampsia. The population in this study were pregnant women in the third trimester who experienced mild and severe preeclampsia at the Muhammadiyah Hospital in Palembang. The sample in this study was pregnant women in the third trimester who experienced mild preeclampsia at the Muhammadiyah Hospital in Palembang as many as 11 people. The instruments used in this study were questionnaires to measure anxiety Stai-Y1 and Stai-Y2, observation sheets and murottal Al-Quran. Results of the study. Conclusion: listening to murottal Al-Quran can reduce the anxiety of pregnant women with mild and severe preeclampsia.